Optimizing Learning Management System to Teach English Grammar - Isnaini Nur Safitri; Pritantina Yuni Lestari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2021)
This study aimed to investigate the use of the Learning Management System (LMS) to teach English Grammar subject in online learning during a covid-19 outbreak. This study was descriptive qualitative research with second-semester students as the subjects of the study. They were students from the English department taking Structure 2 as the compulsory subject. The data were collected by conducting a survey to 71 students who were purposely selected to know the optimization of using LMS in teaching English Grammar during the covid -19 outbreak. The questionnaire was used to do a survey. The results show that the materials uploaded in the LMS are useful to help students understand English Grammar, especially for the topic taught in the second semester. Furthermore, the use of quiz features in LMS can motivate them to learn since they can know the results and the correct answer directly from the LMS. It also can increase students' confidence when doing the same test. However, it was found that the use of LMS cannot replace the direct explanation method from the teacher which is still stated as an effective way of teaching English Grammar subjects.